Seismic effects on leaning slender structures and tall buildings. (1st November 2019) - Bońkowski, Piotr Adam; Zembaty, Zbigniew; Minch, Maciej Yan
Highlights: Mine tremors and natural earthquake effects on leaning towers and tall buildings are analysed. The influence of initial tilt of structures on their seismic vibrations is studied. Technical recommendations for buildings located in subsiding, deep mining areas are examined. Non-linear seismic response analyses for upright and leaning structures are compared. Specific, differences in seismic vibrations in the upper and lower part of tilted structures are pointed out. Abstract: A problem of joint effects of a structural leaning and seismic excitations can be particularly important for tall buildings and slender towers. Present paper addresses problems of loss of seismic resistance of leaning tall structures on examples of two selected typical structures: a 160 m high industrial chimney and a slender 30-storey high building. The problem is discussed first for strong seismic rockburst excitations (induced seismicity – where structural leaning often occurs) and also for strong natural earthquakes. Dynamic, non-linear time-history seismic response analyses of the 160 m high, reinforced concrete industrial chimney and the 30-storey shear wall building are carried out. Detailed parametric analyses of non-linear interaction of the effect of initial leaning and simultaneous seismic action, in form of inelastic time-history analyses, are performed. Unique changes in seismic responses of the leaning structures depending on combinations of various initial foundation tilts and seismic intensities are observed and studied in detail. It is demonstrated that the limitations on structural leaning described in an actual industrial mining code of practice are enough conservative. Various mechanisms driving seismic response at base and in the upper part of a leaning structure are recognized and carefully analysed for various combinations of initial ground tilts and seismic intensities.